The Divergent Pattern of SARS-CoV-2 Variant Predominance and Transmission Dynamics in the Brazilian Island of Ilhabela - Viala, Vincent Louis; Slavov, Svetoslav Nanev; Lima, Loyze Paola Oliveira de; Lima, Alex Ranieri Jeronimo; Ribeiro, Gabriela; Martins, Antonio Jorge; Petry, Bruna; Banhode Souza Todao Lacerda; Poleti, Mirele Daiana; Assato, Patricia Akemi [UNESP]; Cattony Neto, Pedro De Queiroz; Cassano, Raquel de Lello Rocha Campos; et al. (MDPI, 2022)
Our effort in SARS-CoV-2 genomic surveillance in Brazil has detected the Alpha Variant of Concern with a predominance higher than 75% in the population of Ilhabela island (São Paulo State) at a time when the Gamma VOC was already predominating the mainland raised concerns for closer surveillance on this island. Therefore, we intensified the surveillance for 24 weeks by generating data from 34% of local positive cases. Our data show that the patterns of VOC predominance dynamics and infection rates were in general distinct from the mainland. We report here the first known case of Alpha predominance in a Brazilian population, a delay greater than 3 months for the Gamma to dominate the previous variants compared to the mainland, and a faster dispersion rate of Gamma and Delta VOCs compared to the mainland. Phylogenetic analysis revealed the SARS-CoV-2 transmission dynamics in Ilhabela were characterized by multiple independent introduction events of Gamma and Delta, with a few events of Alpha introduction, two of them followed by community transmission. This study evidenced the peculiar behavior of SARS-CoV-2 variants in an isolated population and brought to light the importance of specific programs for SARS-CoV-2 genomic surveillance in isolated populations.
Keywords: Brazil; molecular epidemiology; SARS-CoV-2; variants of concern (VOC)